Water swelling resistant nitrile gloves and preparation method thereof
By using a combination of high nitrile latex and specific additives and using deionized water leaching in the preparation process, the problem of nitrile gloves swelling after soaking in water is solved, and the water resistance and wearability of the gloves are significantly improved.
Patent Information
- Application Number
- CN202411698681.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-04
AI Technical Summary
Existing nitrile gloves will experience obvious swelling after soaking in water for a long time, resulting in larger size and lighter color, and will not fit closely with the hands, making the wearable feel worse.
The combination of high nitrile latex and wax emulsions, surfactants and defoamers in a specific proportion is used to increase the intermolecular force through vulcanization and crosslinking reactions, and leaching is used in the preparation process to enhance the hydrophobicity of the gloves.
The water resistance and wearability of nitrile gloves are significantly improved. The size and color of the gloves have no significant changes in size and color under water conditions of more than 12 hours, and can fit closely with the hands, making them feel good in wear.
Smart Images

Figure BDA0005152721510000011 
Figure BDA0005152721510000021 
Figure BDA0005152721510000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gloves, and particularly relates to water swelling resistant nitrile gloves and a preparation method thereof. Background Art
[0002] As an important personal protective equipment, nitrile gloves have been widely used in many fields such as medical, chemical, and food processing. Its excellent oil and chemical resistance and good wearing comfort make nitrile gloves an indispensable safety protection tool in many working environments. However, in the preparation process of the prior art, the water resistance of nitrile gloves has always been a problem to be solved.
[0003] The traditional method of preparing nitrile gloves usually uses latex with medium or low nitrile content as the main raw material, and is prepared by adding appropriate amounts of additives such as vulcanizing agents and cross-linking agents, and undergoing vulcanization, molding and other process steps. However, the nitrile gloves obtained by this preparation method will swell significantly after being soaked in water for a long time, causing the gloves to become larger in size, lighter in color, and unable to fit the hands tightly, resulting in a poor wearing feel. This not only affects the use effect of the gloves, but may also pose a potential threat to the safety of the user's hands.
[0004] In summary, the obvious deficiencies in water resistance and wearing performance of nitrile gloves prepared by the prior art need to be urgently addressed. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a water-swellable nitrile glove having good water resistance and wearability.
[0006] The invention also provides a preparation method thereof, which is scientific, reasonable and suitable for large-scale production.
[0007] The water-swellable nitrile gloves of the present invention include the following raw materials in parts by weight:
[0008]
[0009]
[0010] The wax emulsion is a mixture of nonionic paraffin emulsion, anionic paraffin emulsion and polyethylene wax emulsion in a mass ratio of (2-4):(1-2):(1-2).
[0011] The high nitrile latex is produced by Qixiang Tengda Chemical Co., Ltd., with an acrylonitrile content of 35%-45%, a total solid content of 45%-48%, a relative density of 0.98-1.01, and a viscosity of 40-60 mPa·s.
[0012] The mass ratio of solid to liquid in the potassium hydroxide aqueous solution, sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion and antioxidant dispersion is 1:2, and the liquid is deionized water.
[0013] The accelerator is one or more of zinc di-n-butyl dithiocarbamate, zinc diethyl dithiocarbamate, and zinc N-pentamethylene dithiocarbamate.
[0014] The surfactant is one or more of sodium dodecylbenzene sulfonate, sodium lauryl sulfate, sodium fatty acid methyl ester sulfonate, and sodium oleyloxyethane sulfonate.
[0015] The defoamer is any one of a polyether defoamer and a mineral oil defoamer.
[0016] The antioxidant is any one of antioxidant AW and antioxidant D.
[0017] Preferably, the nonionic paraffin wax emulsion is Nanjing Tianshi wax emulsion LW-104B, the anionic paraffin wax emulsion is Nanjing Tianshi wax emulsion LW-290, and the polyethylene wax emulsion is Nanjing Tianshi wax emulsion LW-107.
[0018] The method for preparing the water-swellable nitrile gloves of the present invention comprises the following steps:
[0019] (1) Preparation of high nitrile latex mixture:
[0020] Add high nitrile latex into a vulcanizing kettle, stir at a speed of 100-300 r / min, add surfactant and potassium hydroxide aqueous solution; add sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion, antioxidant dispersion, crosslinking agent, wax emulsion and deionized water into the vulcanizing kettle at intervals, continue stirring at a speed of 100-300 r / min for 24 hours, add defoamer and stir evenly to obtain a water-swellable high nitrile latex mixture;
[0021] (2) Preparation of coagulant:
[0022] Add 240-300 parts of deionized water, 90-100 parts of calcium nitrate, and 8-11 parts of a release agent into a reaction container, and stir at a speed of 100-300 r / min for 24 hours to obtain a coagulant mixture;
[0023] (3) placing the hand model in an oven and heating it to 65-70° C., dipping it in the coagulant mixture, and placing the hand model in the oven to dry;
[0024] (4) dipping the dried hand mold into the high nitrile latex mixture, placing the hand mold in an oven for drying, dipping the hand mold into the high nitrile latex mixture again, and placing the hand mold in an oven for drying;
[0025] (5) placing the hand mold in 40-50° C. deionized water for leaching, and then placing it in an oven for drying and curling;
[0026] (6) drying the hand mold in an oven at 100-130° C. for 0.2-1 h, then leaching the hand mold in deionized water at 40-50° C., and then drying the hand mold in an oven to obtain a finished product;
[0027] The conductivity of the deionized water in step (5) and step (6) is 0.055 to 1 μs / cm.
[0028] The release agent described in step (2) is calcium stearate; the interval time for adding the release agent in step (1) is 0.5-1h.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The high nitrile latex with the preferred index of the present invention increases the crosslinking density during vulcanization by adjusting the dosage of sulfur and crosslinking agent, thereby increasing the intermolecular force, making the product more water-resistant, and improving the wearing performance of the gloves after being wetted with water.
[0031] (2) The present invention can improve the stability of the latex system by adding the preferred wax emulsion compound, form a dense accumulation on the film during the latex film-forming process, and migrate to the surface to form a protective film during the latex film-forming process, thereby making the product have good hydrophobicity and giving the product better anti-adhesion and wear resistance.
[0032] (3) In the preparation process, the present invention uses deionized water with a conductivity of 0.055 to 1 us / cm for leaching. By controlling the leaching temperature and time, the hydrophilic substances in the latex can be well washed out, the hydrophobicity of the product is enhanced, and the water resistance of the gloves is greatly improved.
[0033] (4) The conventionally prepared nitrile gloves in the prior art will swell significantly after being soaked in water for about 2 hours, and the color of the gloves will become lighter and whiter. The gloves cannot fit the hands well and have a poor wearing feeling. The gloves made by the method of the present invention can withstand water blistering for more than 12 hours, and the color and size of the gloves do not change significantly. After being soaked in water, the gloves can still fit the hands well and have a good wearing feeling. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto.
[0035] Unless otherwise specified, all raw materials used in the examples are commercially available.
[0036] Example 1
[0037] The water-swellable nitrile gloves include the following raw materials in parts by weight:
[0038] 100 parts of high nitrile latex, 1 part of potassium hydroxide aqueous solution, 2 parts of sulfur dispersion, 2 parts of zinc oxide dispersion, 1 part of accelerator dispersion, 1 part of surfactant, 3 parts of titanium dioxide dispersion, 1 part of defoamer, 1 part of antioxidant dispersion, 1 part of cross-linking agent, 3 parts of wax emulsion, and 180 parts of deionized water.
[0039] The mass ratio of solid to liquid in the potassium hydroxide aqueous solution, sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion and antioxidant dispersion is 1:2, and the liquid is deionized water.
[0040] High nitrile latex is produced by Qixiang Tengda Chemical Co., Ltd., with an acrylonitrile content of 42%, a total solid content of 46%, a relative density of 0.99, and a viscosity of 45 mPa·s. The accelerator is zinc di-n-butyl dithiocarbamate and zinc N-pentamethylene dithiocarbamate (mass ratio is 1:1), the surfactant is sodium dodecylbenzene sulfonate and sodium fatty acid methyl ester sulfonate (mass ratio is 2:1), the defoamer is a mineral oil defoamer (defoamer GL-58 of Qingdao Enze Chemical Co., Ltd.), the antioxidant is antioxidant D, and the crosslinker is a carbodiimide crosslinker. The wax emulsion is a mixture of non-ionic paraffin emulsion (Nanjing Tianshi wax emulsion LW-104B), anionic wax emulsion (Nanjing Tianshi wax emulsion LW-290) and polyethylene wax emulsion (Nanjing Tianshi wax emulsion LW-107) in a mass ratio of 4:1:1.
[0041] The method for preparing the water-swellable nitrile gloves comprises the following steps:
[0042] (1) Preparation of high nitrile latex mixture:
[0043] Add high nitrile latex to the vulcanizing kettle, stir at a speed of 200r / min, and add surfactant and potassium hydroxide aqueous solution in sequence. Add sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion, antioxidant dispersion, crosslinking agent, wax emulsion, and deionized water to the vulcanizing kettle in sequence every half an hour, stir at a speed of 200r / min for 24 hours, add defoamer and stir evenly to obtain a water-swellable high nitrile latex mixture.
[0044] (2) Preparation of coagulant: 260 parts of deionized water, 95 parts of calcium nitrate, and 8 parts of a release agent (calcium stearate) were added to a reaction container in sequence, and stirred at a speed of 150 r / min for 24 hours to obtain a coagulant mixture.
[0045] (3) Place the hand model in an oven and heat it to 65°C, immerse it in the coagulant mixture, and place the hand model in an oven to dry.
[0046] (4) Dipping the dried hand model in the high nitrile latex mixture, and placing the hand model in an oven for drying. Dipping the hand model in the high nitrile latex mixture again, and placing the hand model in an oven for drying.
[0047] (5) The hand mold is placed in 40° C. deionized water for leaching, and then placed in an oven for drying and curling.
[0048] (6) The hand mold is placed in a 100° C. oven for drying for 0.5 h, then placed in 40° C. deionized water for leaching, and then placed in an oven for drying to produce a finished product.
[0049] The conductivity of the deionized water in step (5) and step (6) is 0.072 μs / cm.
[0050] Example 2
[0051] The water-swellable nitrile gloves include the following raw materials in parts by weight:
[0052] 100 parts of high nitrile latex, 1 part of potassium hydroxide aqueous solution, 2 parts of sulfur dispersion, 2 parts of zinc oxide dispersion, 1 part of accelerator dispersion, 1 part of surfactant, 3 parts of titanium dioxide dispersion, 1 part of defoamer, 1 part of antioxidant dispersion, 1 part of cross-linking agent, 3 parts of wax emulsion, and 180 parts of deionized water.
[0053] The mass ratio of solid to liquid in the potassium hydroxide aqueous solution, sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion and antioxidant dispersion is 1:2, and the liquid is deionized water.
[0054] High nitrile latex is produced by Qixiang Tengda Chemical Co., Ltd., with an acrylonitrile content of 42%, a total solid content of 46%, a relative density of 0.99, and a viscosity of 45 mPa·s. The accelerator is zinc di-n-butyl dithiocarbamate and zinc N-pentamethylene dithiocarbamate (mass ratio is 1:1), the surfactant is sodium dodecylbenzene sulfonate and sodium fatty acid methyl ester sulfonate (mass ratio is 2:1), the defoamer is a mineral oil defoamer (defoamer GL-58 of Qingdao Enze Chemical Co., Ltd.), the antioxidant is antioxidant D, and the crosslinker is a carbodiimide crosslinker. The wax emulsion is a mixture of non-ionic paraffin emulsion (Nanjing Tianshi wax emulsion LW-104B), anionic wax emulsion (Nanjing Tianshi wax emulsion LW-290) and polyethylene wax emulsion (Nanjing Tianshi wax emulsion LW-107) in a mass ratio of 3:2:1.
[0055] The method for preparing the water-swellable nitrile gloves comprises the following steps:
[0056] (1) Preparation of high nitrile latex mixture:
[0057] Add high nitrile latex to the vulcanizing kettle, stir at a speed of 200r / min, and add surfactant and potassium hydroxide aqueous solution in sequence. Add sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion, antioxidant dispersion, crosslinking agent, wax emulsion, and deionized water to the vulcanizing kettle in sequence every half an hour, stir at a speed of 200r / min for 24 hours, add defoamer and stir evenly to obtain a water-swellable high nitrile latex mixture.
[0058] (2) Preparation of coagulant: 260 parts of deionized water, 95 parts of calcium nitrate, and 8 parts of a release agent (calcium stearate) were added to a reaction container in sequence, and stirred at a speed of 150 r / min for 24 hours to obtain a coagulant mixture.
[0059] (3) Place the hand model in an oven and heat it to 65°C, immerse it in the coagulant mixture, and place the hand model in an oven to dry.
[0060] (4) Dipping the dried hand model in the high nitrile latex mixture, and placing the hand model in an oven for drying. Dipping the hand model in the high nitrile latex mixture again, and placing the hand model in an oven for drying.
[0061] (5) The hand mold is placed in 40° C. deionized water for leaching, and then placed in an oven for drying and curling.
[0062] (6) The hand mold is placed in a 100° C. oven for drying for 0.5 h, then placed in 40° C. deionized water for leaching, and then placed in an oven for drying to produce a finished product.
[0063] The conductivity of the deionized water in step (5) and step (6) is 0.072 μs / cm.
[0064] Example 3
[0065] The water-swellable nitrile gloves include the following raw materials in parts by weight:
[0066] 100 parts of high nitrile latex, 1 part of potassium hydroxide aqueous solution, 2 parts of sulfur dispersion, 2 parts of zinc oxide dispersion, 1 part of accelerator dispersion, 1 part of surfactant, 3 parts of titanium dioxide dispersion, 1 part of defoamer, 1 part of antioxidant dispersion, 1 part of cross-linking agent, 3 parts of wax emulsion, and 180 parts of deionized water.
[0067] The mass ratio of solid to liquid in the potassium hydroxide aqueous solution, sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion and antioxidant dispersion is 1:2, and the liquid is deionized water.
[0068] High nitrile latex is produced by Qixiang Tengda Chemical Co., Ltd., with an acrylonitrile content of 42%, a total solid content of 46%, a relative density of 0.99, and a viscosity of 45 mPa·s. The accelerator is zinc di-n-butyl dithiocarbamate and zinc N-pentamethylene dithiocarbamate (mass ratio is 1:1), the surfactant is sodium dodecylbenzene sulfonate and sodium fatty acid methyl ester sulfonate (mass ratio is 2:1), the defoamer is a mineral oil defoamer (defoamer GL-58 of Qingdao Enze Chemical Co., Ltd.), the antioxidant is antioxidant D, and the crosslinker is a carbodiimide crosslinker. The wax emulsion is a mixture of non-ionic paraffin emulsion (Nanjing Tianshi wax emulsion LW-104B), anionic wax emulsion (Nanjing Tianshi wax emulsion LW-290) and polyethylene wax emulsion (Nanjing Tianshi wax emulsion LW-107) in a mass ratio of 2:1:1.
[0069] The method for preparing the water-swellable nitrile gloves comprises the following steps:
[0070] (1) Preparation of high nitrile latex mixture:
[0071] Add high nitrile latex to the vulcanizing kettle, stir at a speed of 200r / min, and add surfactant and potassium hydroxide aqueous solution in sequence. Add sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion, antioxidant dispersion, crosslinking agent, wax emulsion, and deionized water to the vulcanizing kettle in sequence every half an hour, stir at a speed of 200r / min for 24 hours, add defoamer and stir evenly to obtain a water-swellable high nitrile latex mixture.
[0072] (2) Preparation of coagulant: 260 parts of deionized water, 95 parts of calcium nitrate, and 8 parts of a release agent (calcium stearate) were added to a reaction container in sequence, and stirred at a speed of 150 r / min for 24 hours to obtain a coagulant mixture.
[0073] (3) Place the hand model in an oven and heat it to 65°C, immerse it in the coagulant mixture, and place the hand model in an oven to dry.
[0074] (4) Dipping the dried hand model in the high nitrile latex mixture, and placing the hand model in an oven for drying. Dipping the hand model in the high nitrile latex mixture again, and placing the hand model in an oven for drying.
[0075] (5) The hand mold is placed in 40° C. deionized water for leaching, and then placed in an oven for drying and curling.
[0076] (6) The hand mold is placed in a 100° C. oven for drying for 0.5 h, then placed in 40° C. deionized water for leaching, and then placed in an oven for drying to produce a finished product.
[0077] The conductivity of the deionized water in step (5) and step (6) is 0.072 μs / cm.
[0078] Example 4
[0079] The water-swellable nitrile gloves include the following raw materials in parts by weight:
[0080] 110 parts of high nitrile latex, 1.5 parts of potassium hydroxide aqueous solution, 3 parts of sulfur dispersion, 3 parts of zinc oxide dispersion, 2 parts of accelerator dispersion, 0.5 parts of surfactant, 4 parts of titanium dioxide dispersion, 3 parts of defoaming agent, 2 parts of antioxidant dispersion, 2 parts of crosslinking agent, 5 parts of wax emulsion, and 200 parts of deionized water.
[0081] The mass ratio of solid to liquid in the potassium hydroxide aqueous solution, sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion and antioxidant dispersion is 1:2, and the liquid is deionized water.
[0082] The high nitrile latex is produced by Qixiang Tengda Chemical Co., Ltd., with an acrylonitrile content of 42%, a total solid content of 46%, a relative density of 0.99, and a viscosity of 45 mPa·s. The accelerator is zinc dibutyl dithiocarbamate and zinc diethyl dithiocarbamate (mass ratio is 2:1), the surfactant is sodium dodecylbenzene sulfonate, the defoamer is a polyether defoamer (Guangzhou Xinlian Chemical Technology Co., Ltd. defoamer 3062), the antioxidant is antioxidant AW, and the crosslinker is carbodiimide crosslinker and 3-isocyanate propyl trimethoxy silane crosslinker (mass ratio is 1:1). The 3-isocyanate propyl trimethoxy silane crosslinker is kh-901 from Hangzhou Jessica Chemical Co., Ltd. The wax emulsion is a mixture of non-ionic paraffin emulsion (Nanjing Tianshi wax emulsion LW-104B), anionic wax emulsion (Nanjing Tianshi wax emulsion LW-290) and polyethylene wax emulsion (Nanjing Tianshi wax emulsion LW-107) in a mass ratio of 2:1:1.
[0083] The method for preparing the water-swellable nitrile gloves comprises the following steps:
[0084] (1) Preparation of high nitrile latex mixture:
[0085] Add high nitrile latex to the vulcanizing kettle, stir at a speed of 300r / min, add surfactant and potassium hydroxide aqueous solution in sequence. Add sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion, antioxidant dispersion, crosslinking agent, wax emulsion and deionized water to the vulcanizing kettle in sequence every half an hour, stir at a speed of 300r / min for 24h, add defoamer and stir evenly to obtain a water-swellable high nitrile latex mixture.
[0086] (2) Preparation of coagulant:
[0087] 280 parts of deionized water, 100 parts of calcium nitrate, and 9 parts of a release agent (calcium stearate) were added to a reaction container in sequence, and stirred at a speed of 200 r / min for 24 hours to obtain a coagulant mixed solution.
[0088] (3) Place the hand model in an oven and heat it to 70°C, immerse it in the coagulant mixture, and place the hand model in an oven to dry.
[0089] (4) Dipping the dried hand model in the high nitrile latex mixture, and placing the hand model in an oven for drying. Dipping the hand model in the high nitrile latex mixture again, and placing the hand model in an oven for drying.
[0090] (5) The hand mold is placed in 50° C. deionized water for leaching, and then placed in an oven for drying and curling.
[0091] (6) The hand mold is placed in a 110° C. oven for drying for 0.6 h, then placed in 50° C. deionized water for leaching, and then placed in an oven for drying to produce a finished product.
[0092] The conductivity of the deionized water in step (5) and step (6) is 0.084 μs / cm.
[0093] Comparative Example 1
[0094] The water-swellable nitrile gloves include the following raw materials in parts by weight:
[0095] 100 parts of high nitrile latex, 1 part of potassium hydroxide aqueous solution, 2 parts of sulfur dispersion, 2 parts of zinc oxide dispersion, 1 part of accelerator dispersion, 1 part of surfactant, 3 parts of titanium dioxide dispersion, 1 part of defoamer, 1 part of antioxidant dispersion, 1 part of cross-linking agent, 3 parts of wax emulsion, and 180 parts of deionized water.
[0096] The mass ratio of solid to liquid in the potassium hydroxide aqueous solution, sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion and antioxidant dispersion is 1:2, and the liquid is deionized water.
[0097] The high nitrile latex is produced by Qixiang Tengda Chemical Co., Ltd., with an acrylonitrile content of 42%, a total solid content of 46%, a relative density of 0.99, and a viscosity of 45 mPa·s. The accelerator is zinc di-n-butyl dithiocarbamate and zinc N-pentamethylene dithiocarbamate (mass ratio is 1:1), the surfactant is sodium dodecylbenzene sulfonate and sodium fatty acid methyl ester sulfonate (mass ratio is 2:1), the defoamer is a mineral oil defoamer (defoamer GL-58 of Qingdao Enze Chemical Co., Ltd.), the antioxidant is antioxidant D, and the crosslinker is a carbodiimide crosslinker. The wax emulsion is a mixture of non-ionic paraffin emulsion (Nanjing Tianshi wax emulsion LW-104B), anionic wax emulsion (Nanjing Tianshi wax emulsion LW-290) and polyethylene wax emulsion (Nanjing Tianshi wax emulsion LW-107) in a mass ratio of 1:3:3.
[0098] The method for preparing the water-swellable nitrile gloves comprises the following steps:
[0099] (1) Preparation of high nitrile latex mixture:
[0100] Add high nitrile latex to the vulcanizing kettle, stir at a speed of 200r / min, and add surfactant and potassium hydroxide aqueous solution in sequence. Add sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion, antioxidant dispersion, crosslinking agent, wax emulsion, and deionized water to the vulcanizing kettle in sequence every half an hour, stir at a speed of 200r / min for 24 hours, add defoamer and stir evenly to obtain a water-swellable high nitrile latex mixture.
[0101] (2) Preparation of coagulant: 260 parts of deionized water, 95 parts of calcium nitrate, and 8 parts of a release agent (calcium stearate) were added to a reaction container in sequence, and stirred at a speed of 150 r / min for 24 hours to obtain a coagulant mixture.
[0102] (3) Place the hand model in an oven and heat it to 65°C, immerse it in the coagulant mixture, and place the hand model in an oven to dry.
[0103] (4) Dipping the dried hand model in the high nitrile latex mixture, and placing the hand model in an oven for drying. Dipping the hand model in the high nitrile latex mixture again, and placing the hand model in an oven for drying.
[0104] (5) The hand mold is placed in 40° C. deionized water for leaching, and then placed in an oven for drying and curling.
[0105] (6) The hand mold is placed in a 100° C. oven for drying for 0.5 h, then placed in 40° C. deionized water for leaching, and then placed in an oven for drying to produce a finished product.
[0106] The conductivity of the deionized water in step (5) and step (6) is 0.065 μs / cm.
[0107] Comparative Example 2
[0108] The water-swellable nitrile gloves include the following raw materials in parts by weight:
[0109] 100 parts of high nitrile latex, 1 part of potassium hydroxide aqueous solution, 2 parts of sulfur dispersion, 2 parts of zinc oxide dispersion, 1 part of accelerator dispersion, 1 part of surfactant, 3 parts of titanium dioxide dispersion, 1 part of defoamer, 1 part of antioxidant dispersion, 1 part of cross-linking agent, 3 parts of wax emulsion, and 180 parts of deionized water.
[0110] The mass ratio of solid to liquid in the potassium hydroxide aqueous solution, sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion and antioxidant dispersion is 1:2, and the liquid is deionized water.
[0111] High nitrile latex is produced by Qixiang Tengda Chemical Co., Ltd., with an acrylonitrile content of 42%, a total solid content of 46%, a relative density of 0.99, and a viscosity of 45 mPa·s. The accelerator is zinc di-n-butyl dithiocarbamate and zinc N-pentamethylene dithiocarbamate (mass ratio is 1:1), the surfactant is sodium dodecylbenzene sulfonate and sodium fatty acid methyl ester sulfonate (mass ratio is 2:1), the defoamer is a mineral oil defoamer (defoamer GL-58 of Qingdao Enze Chemical Co., Ltd.), the antioxidant is antioxidant D, and the crosslinker is a carbodiimide crosslinker. The wax emulsion is a mixture of non-ionic paraffin emulsion (Nanjing Tianshi wax emulsion LW-104B), anionic wax emulsion (Nanjing Tianshi wax emulsion LW-290) and polyethylene wax emulsion (Nanjing Tianshi wax emulsion LW-107) in a mass ratio of 2:1:1.
[0112] The method for preparing the water-swellable nitrile gloves comprises the following steps:
[0113] (1) Preparation of high nitrile latex mixture:
[0114] Add high nitrile latex to the vulcanizing kettle, stir at a speed of 200r / min, add surfactant and potassium hydroxide aqueous solution. Add sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion, antioxidant dispersion, crosslinking agent, wax emulsion and deionized water to the vulcanizing kettle in turn every half an hour, stir at a speed of 200r / min for 24 hours, add defoamer and stir evenly to obtain a water-swellable high nitrile latex mixture.
[0115] (2) Preparation of coagulant: 260 parts of deionized water, 95 parts of calcium nitrate, and 8 parts of a release agent (calcium stearate) were added to a reaction container in sequence, and stirred at a speed of 150 r / min for 24 hours to obtain a coagulant mixture.
[0116] (3) Place the hand model in an oven and heat it to 65°C, immerse it in the coagulant mixture, and place the hand model in an oven to dry.
[0117] (4) Dipping the dried hand model in the high nitrile latex mixture, and placing the hand model in an oven for drying. Dipping the hand model in the high nitrile latex mixture again, and placing the hand model in an oven for drying.
[0118] (5) The hand mold is placed in 40° C. deionized water for leaching, and then placed in an oven for drying and curling.
[0119] (6) The hand mold is placed in a 100° C. oven for drying for 0.5 h, then placed in 40° C. deionized water for leaching, and then placed in an oven for drying to produce a finished product.
[0120] The conductivity of the deionized water in step (5) and step (6) is 5 μs / cm.
[0121] Comparative Example 3
[0122] The water-swellable nitrile gloves include the following raw materials in parts by weight:
[0123] 100 parts of high nitrile latex, 1 part of potassium hydroxide aqueous solution, 2 parts of sulfur dispersion, 2 parts of zinc oxide dispersion, 1 part of accelerator dispersion, 1 part of surfactant, 3 parts of titanium dioxide dispersion, 1 part of defoamer, 1 part of antioxidant dispersion, 1 part of cross-linking agent, 3 parts of wax emulsion, and 180 parts of deionized water.
[0124] The mass ratio of solid to liquid in the potassium hydroxide aqueous solution, sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion and antioxidant dispersion is 1:2, and the liquid is deionized water.
[0125] The accelerator is zinc di-n-butyl dithiocarbamate and zinc N-pentamethylene dithiocarbamate (mass ratio is 1:1), the surfactant is sodium dodecylbenzene sulfonate and sodium fatty acid methyl ester sulfonate (mass ratio is 2:1), the defoamer is a mineral oil defoamer (defoamer GL-58 of Qingdao Enze Chemical Co., Ltd.), the antioxidant is antioxidant D, and the crosslinker is a carbodiimide crosslinker. The wax emulsion is a mixture of non-ionic paraffin emulsion (Nanjing Tianshi wax emulsion LW-104B), anionic wax emulsion (Nanjing Tianshi wax emulsion LW-290) and polyethylene wax emulsion (Nanjing Tianshi wax emulsion LW-107) in a mass ratio of 2:1:1.
[0126] The method for preparing the water-swellable nitrile gloves comprises the following steps:
[0127] (1) Preparation of high nitrile latex mixture:
[0128] Add high nitrile latex to the vulcanizing kettle, stir at a speed of 200r / min, and add surfactant and potassium hydroxide aqueous solution in sequence. Add sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion, antioxidant dispersion, crosslinking agent, wax emulsion, and deionized water to the vulcanizing kettle in sequence every half an hour, stir at a speed of 200r / min for 24 hours, add defoamer and stir evenly to obtain a water-swellable high nitrile latex mixture.
[0129] (2) Preparation of coagulant: 260 parts of deionized water, 95 parts of calcium nitrate, and 8 parts of a release agent (calcium stearate) were added to a reaction container in sequence, and stirred at a speed of 150 r / min for 24 hours to obtain a coagulant mixture.
[0130] (3) Place the hand model in an oven and heat it to 65°C, immerse it in the coagulant mixture, and place the hand model in an oven to dry.
[0131] (4) Dipping the dried hand model in the high nitrile latex mixture, and placing the hand model in an oven for drying. Dipping the hand model in the high nitrile latex mixture again, and placing the hand model in an oven for drying.
[0132] (5) The hand mold is placed in 40° C. deionized water for leaching, and then placed in an oven for drying and curling.
[0133] (6) The hand mold is placed in a 100° C. oven for drying for 0.5 h, then placed in 40° C. deionized water for leaching, and then placed in an oven for drying to produce a finished product.
[0134] The high nitrile latex in step (1) is provided by Shandong Guangpu Biotechnology Co., Ltd., and has an acrylonitrile content of 41%, a total solid content of 45%, a relative density of 0.98, and a viscosity of 42 mPa·s.
[0135] The conductivity of the deionized water in step (5) and step (6) is 0.52 μs / cm.
[0136] Performance Testing
[0137] Test method: The water swelling resistant high nitrile latex gloves in the embodiment and the comparative example were subjected to a water soaking test respectively, and the soaking test was carried out in a water container at 25±2°C for 2h and 12h. The specific test results are shown in Table 1.
[0138] Table 1 Test results
[0139]
[0140] As shown in Table 1, compared with the comparative example product, the water-swellable products in Examples 1-4 have no obvious size changes after 12 hours of soaking in water, and do not affect wearing. The gloves in Comparative Examples 1-3 become obviously larger after 2 hours of soaking in water, affecting wearing, and the color changes significantly.
[0141] The above embodiments are only used to illustrate the technical solutions of the present invention and are not used to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A water swelling resistant nitrile glove, characterized in that: Including the following raw materials by mass: The wax emulsion is a mixture of nonionic paraffin emulsion, anionic paraffin emulsion and polyethylene wax emulsion in a mass ratio of (2-4):(1-2):(1-2).
2. The water swelling resistant nitrile gloves according to claim 1, characterized in that: The high nitrile latex has an acrylonitrile content of 35%-45%, a total solid content of 45%-48%, a relative density of 0.98-1.01, and a viscosity of 40-60 mPa·s.
3. The water swelling resistant nitrile gloves according to claim 1, characterized in that: The mass ratio of solid to liquid in the potassium hydroxide aqueous solution, sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion and antioxidant dispersion is 1:2, and the liquid is deionized water.
4. The water swelling resistant nitrile gloves according to claim 1, characterized in that: The accelerator is one or more of zinc di-n-butyl dithiocarbamate, zinc diethyl dithiocarbamate, and zinc N-pentamethylene dithiocarbamate.
5. The water swelling resistant nitrile gloves according to claim 1, characterized in that: The surfactant is one or more of sodium dodecylbenzene sulfonate, sodium lauryl sulfate, sodium fatty acid methyl ester sulfonate, and sodium oleyloxyethane sulfonate.
6. The water swelling resistant nitrile gloves according to claim 1, characterized in that: The defoamer is any one of a polyether defoamer and a mineral oil defoamer.
7. The water swelling resistant nitrile gloves according to claim 1, characterized in that: The antioxidant is any one of antioxidant AW and antioxidant D.
8. The water swelling resistant nitrile gloves according to claim 1, characterized in that: The nonionic paraffin wax emulsion is wax emulsion LW-104B, the anionic paraffin wax emulsion is wax emulsion LW-290, and the polyethylene wax emulsion is wax emulsion LW-107.
9. A method for preparing the water-swellable nitrile gloves according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Preparation of high nitrile latex mixture: Add high nitrile latex into a vulcanizing kettle, start stirring, add surfactant and potassium hydroxide aqueous solution; add sulfur dispersion, zinc oxide dispersion, accelerator dispersion, titanium dioxide dispersion, antioxidant dispersion, crosslinking agent, wax emulsion and deionized water into the vulcanizing kettle at intervals, continue stirring, add defoamer and stir evenly to obtain a water-swellable high nitrile latex mixture; (2) Preparation of coagulant: Add 240-300 parts of deionized water, 90-100 parts of calcium nitrate, and 8-11 parts of a release agent into a reaction container and stir evenly to obtain a coagulant mixture; (3) placing the hand model in an oven and heating it to 65-70° C., dipping it in the coagulant mixture, and placing the hand model in the oven to dry; (4) dipping the dried hand mold in the high nitrile latex mixture, placing the hand mold in an oven for drying, dipping the hand mold in the high nitrile latex mixture again, and placing the hand mold in an oven for drying; (5) placing the hand mold in 40-50° C. deionized water for leaching, and then placing it in an oven for drying and curling; (6) drying the hand mold in an oven at 100-130° C. for 0.2-1 h, then leaching the hand mold in deionized water at 40-50° C., and then drying the hand mold in an oven to obtain a finished product; The conductivity of the deionized water in step (5) and step (6) is 0.055 to 1 μs / cm.
10. The method for preparing water-swellable nitrile gloves according to claim 9, characterized in that: The release agent described in step (2) is calcium stearate; the interval time of the interval addition described in step (1) is 0.5-1h.